Effects of Installation Parameters of Drilled Displacement Piles on In Situ Stress Conditions in Stiff Clays - Martin D. Larisch; David J. Williams; Alexander Scheuermann (Deep Foundations Institute, 1900)
"Drilled displacement piles (DDP) have been used around the world for decades as foundation elements for structures and embankments. Typically the pile toes are designed to penetrate into stiff or dense soil formations to achieve sufficient base resistance. Recent research at The University of Queensland in Brisbane, Australia has discovered that the in situ stress conditions in stiff to hard clays is directly related to pile installation rates, which in turn are a function of the piling rig capacity and ground conditions. With adequate and constant pile penetration rates in situ stress conditions in the stiff to hard clay are increased by about 40%, resulting in significantly higher pile capacities. If pile penetration rates are too slow the in situ stress conditions are reduced considerably by remoulding and shearing of the clay, potentially causing reduced pile capacities. The paper presents the results of full-scale test piles at a stiff to hard clay site installed using different full-scale piling equipment.INTRODUCTIONDrilled displacement piling (DDP) is a piling technique in which a hollow stem, fitted with a purpose built displacement tool at the bottom, is drilled into the ground. Dissimilar to non-displacement piles, like Continuous Flight Auger (CFA) piles or conventional rotary bored piles drilled with kelly bars, the soil is not excavated during the DDP penetration process, but is displaced laterally and to a lesser extent vertically. The cavity created by the drilling tool is filled with highly workable concrete during the extraction process. The DDP technique is very economical providing high production rates and creating only marginal drill spoil, which has led to its increased global usage during the last decade. The typical DDP installation process is described in Figure 1."